2019
DOI: 10.1007/s12649-019-00655-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of a Method for Obtaining Brown Coal and Biochar Based Granular Compound Fertilizer

Abstract: A purpose of the research was to develop a method for the preparation of novel organo-mineral fertilizers with the use of brown coal and biochars as organic additives. Brown coal was blended simultaneously together with inorganic materials used for the process of urea superphosphate production in a laboratory scale using a pan granulator and in larger scale using a rapid mixer granulator. Biochars were used for the coating purposes of the urea superphosphate granules on a laboratory scale using a pan granulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Biochar was analyzed for pH using the glass electrode method and biochar carbon was determined by the loss on ignition protocol by subjecting biochar to relatively high temperature (550 °C) for 4 h ( Mikos-Szymańska et al., 2019 ). Micro Kjeldahl method was followed to analyse for total nitrogen in biochar ( Allen et al., 1974 ) and ammonium phosphomolybdate protocol was used for total phosphorus determination ( Motsara and Roy, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Biochar was analyzed for pH using the glass electrode method and biochar carbon was determined by the loss on ignition protocol by subjecting biochar to relatively high temperature (550 °C) for 4 h ( Mikos-Szymańska et al., 2019 ). Micro Kjeldahl method was followed to analyse for total nitrogen in biochar ( Allen et al., 1974 ) and ammonium phosphomolybdate protocol was used for total phosphorus determination ( Motsara and Roy, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Electrical conductivity (EC) of biochar was determined using conductivity meter (LF91, Germany). Loss on ignition method was used for biochar carbon and ash determination by respectively heating biochar at 550 °C ( Mikos-Szymańska et al., 2019 ) and 900 °C ( Ascough et al., 2018 ) for 4 h. Total nitrogen in biochar was determined using the micro Kjeldahl method as described by Stewarte et al. (1974) .…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the positive effects of the potential fertilizer obtained after WAO, which possesses strong evidence of humic-like substances, supported by previous analyses (i.e., ATR–FTIR, LOI, TGA, pH, and turbidity) and previously reported with the oxidation of wheat straw processed waste by Yao et al , containing plant growth and soil fertility properties, ,,,, a pot trial (bioassay) was performed with alfalfa and soybean that suggested significant plant development when the solid and liquid phases of the selected treatment (CWHPO-240-100-1) were applied.…”
Section: Results and Analysismentioning
confidence: 90%